The impact of virtual immersive public art on the restorative experience of urban residents - Li, Lin; Abdul Shukor, Shureen Faris; Mat Noor, Mohd Sallehuddin; Hasna, Mohd Fabian (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
This study explores the role of virtual immersive public art in improving the psychological well-being of urban residents. The research is set in the context of urban environments, where virtual immersive public art has the potential to foster innovation, integrate technology, and organically blend into public spaces. The study evaluates the impact of such art on psychological restoration by focusing on three key dimensions: interactive themes, interactive mechanisms, and artistic characteristics. A questionnaire survey was conducted to collect participants’ real-life experiences and reactions to these art installations. The results show that virtual immersive public art significantly contributes to the restorative experience of urban residents, offering valuable insights into how these installations can promote mental health. Based on the findings, the study provides practical design recommendations for incorporating virtual immersive public art into future urban planning and design projects to enhance urban living conditions and support psychological recovery.